2014
DOI: 10.5530/ijper.47.4.8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Dynamics of Ibuprofen Incorporated Proniosomal Gel

Abstract: Aim: The research was aimed to encapsulate the ibuprofen with proniosomal gel and facilitate ibuprofen release in sustained manner for sustained drug release. Methods: Different proniosomal gels of ibuprofen were formulated with Span 20/Span 80 and soya lecithin using the method described in literature. In all formulations cholesterol concentration was kept constant. The prepared proniosomal gels were evaluated for chemical incompatibility by FT-IR, vesicle size analysis, encapsulation efficiency, in vitro dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Chowdary and Prapulla studied isovaleric acid esterification in the presence of ethanol catalyzed by Rhizomucor meihei solely with hexane and also with mixed solvents. The reaction was explained using the Ping‐Pong Bi‐Bi mechanism.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…Chowdary and Prapulla studied isovaleric acid esterification in the presence of ethanol catalyzed by Rhizomucor meihei solely with hexane and also with mixed solvents. The reaction was explained using the Ping‐Pong Bi‐Bi mechanism.…”
Section: Resultsmentioning
confidence: 64%
“…The initial increase and subsequent decreasing trend in the reaction rate with the increase in ethanol concentration indicates that ethanol may act as an inhibitor beyond the critical concentration. Previous researchers also reported the inhibition property of ethanol (ethanol concentration > 0.1 mol/L) in esterification reactions . For instance, Dumont et al and Mendez et al showed that adding excess alcohol to a reaction mixture can affect the alkyl ester yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations